Buckling analysis of laminated cylindrical composite shell panel under mechanical and hygrothermal loads - Thinh, Tran Ich; Ngoc, Le Kim (Vietnam Journal of Mechanics, 2005)
This paper deals with buckling of analysis multilaminated cylindrical shell panels subjected to axial and hygrothermal loadings. The geometrical non-linear analysis is carried out using the Finite Element Method based on a single layer first shear deformation theory. A nine-nodal isoparametric element with 5 degrees of freedom per node is considered. The effects of different number of layers, lamination angles, length to width ratios and hygrothermal effects are studied.